A study of the causes of bouncing problems of shock absorber - Mohd Sufian, Jamaludin (2012)
The purpose of the project is to investigate the problems of shock absorber in the market. The shock absorber is commonly use at all vehicle today. There are some problem happen at the vehicle when ride at the bumping road condition. One of the problems is that the vehicle bounce continuously more than one times and it is called as bouncing problems. The objective of this project is to study the causes of the bouncing problem at the vehicle and to compare the failure parts performance in terms of its yield strength between steel and beryllium copper. The scope of study for this project includes, experimental of suspension systems and bouncing problem in vehicle, apply structural analysis and model analysis on the shock absorber and application of Finite Element Analysis (FEA). In this project, after make an experiment and analysis, the problem of bouncing problem of shock absorber is come from the spring. Overall, this project acquires the skills of using software and skills to investigate the problem.